Modelling the 3D Crack Network Observed in Desiccated Soils - Maedo, Michael A.; Sanchez, Marcelo; Manzoli, Osvaldo [UNESP]; Guimaraes, Leonardo; Hoyos, L. R.; McCartney, J. S.; Houston, S. L.; Likos, W. J. (Amer Soc Civil Engineers, 2018)
The study of crack generation and propagation in soils is a very complex problem and possesses several challenges. In this paper a novel approach is proposed to model the formation and propagation of cracks in drying soils. This technique consists of introducing finite elements with high aspect ratio between the regular elements of the original mesh. The main components of the mathematical formulation of the proposed approach are presented, with special emphasis on the constitutive models. Three drying tests were simulated considering circular plates with different heights in order to study the development of desiccation cracks. Thus, the drying process was reproduced by imposing a suction gradient at the top of the soil specimen. The obtained crack patterns were compared against experimental tests to validate the proposed method. The results indicated that the technique was able to capture the main phenomena related to the desiccation crack.